2017
DOI: 10.1021/acs.biochem.7b00722
|View full text |Cite
|
Sign up to set email alerts
|

Heterochiral Knottin Protein: Folding and Solution Structure

Abstract: Homochirality is a general feature of biological macromolecules, and Nature includes few examples of heterochiral proteins. Herein, we report on the design, chemical synthesis, and structural characterization of heterochiral proteins possessing loops of amino acids of chirality opposite to that of the rest of a protein scaffold. Using the protein Ecballium elaterium trypsin inhibitor II, we discover that selective β-alanine substitution favors the efficient folding of our heterochiral constructs. Solution nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…In all cases (20 shown), a single major product containing three disulfide bonds was formed. These data suggest that in a combinatorial library of EETI-II variants, many will be present as folded cystine knots, which likely retain the disulfide connectivity and general tertiary structure of the native EETI-II molecule (37,42).…”
Section: Significancementioning
confidence: 91%
See 1 more Smart Citation
“…In all cases (20 shown), a single major product containing three disulfide bonds was formed. These data suggest that in a combinatorial library of EETI-II variants, many will be present as folded cystine knots, which likely retain the disulfide connectivity and general tertiary structure of the native EETI-II molecule (37,42).…”
Section: Significancementioning
confidence: 91%
“…amenable to chemical synthesis (34), is known to oxidatively fold spontaneously despite sequence variation of the trypsin-binding loop (23,(35)(36)(37)(38), and has been successfully engineered to bind α v β 3 and α v β 5 integrins based on the Arg-Gly-Asp motif using yeast-surface display (39,40). The broad tolerance of the EETI-II molecule to loop expansion and sequence variation (38) is typical of cystine knot proteins generally (41), and we anticipated that this feature could be leveraged to prepare synthetic libraries of folded variants for the selection of novel binding proteins.…”
Section: Significancementioning
confidence: 99%
“…[18] More recently, Pentelute reported heterochiral variants of Ecballium elaterium trypsin inhibitor II, a disulfide-rich miniprotein that has been retargeted toward cell-surface receptors for tumor imaging applications. [19] Replacement of a large exposed loop in the prototype with a D-α-peptide segment led to mimics of the natural protein with similar folds but improved stability to proteolytic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Bulaj showed that the incorporation of ethylene glycol and methylene spacers in place of a Gly‐Gly motif in a loop of the μ‐conotoxin SIIIA led to hybrids exhibiting bioactivities comparable to that of the native toxin . More recently, Pentelute reported heterochiral variants of Ecballium elaterium trypsin inhibitor II, a disulfide‐rich miniprotein that has been retargeted toward cell‐surface receptors for application in tumor imaging . Replacement of a large exposed loop in the prototype with a d ‐α‐peptide segment led to mimics of the natural protein with similar folds but improved stability to proteolytic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Protein domains in which the functionally relevant segment is a surface-exposed loop can also be subject to prosthetic modification, as illustrated by the introduction of a flexible spacer in an ion-channelinhibitory conotoxin 66 and the grafting of an engineered receptorbinding peptide loop onto a disulfide-rich d-α-residue (17)-based knottin scaffold (Fig. 3d) 67 . In both cases, the modification improved stability to degradation by proteolytic enzymes.…”
Section: Partially Artificial Backbonesmentioning
confidence: 99%